Piezoelectric potential activated interfacial electric field in BiFeO3@BaTiO3 heterojunction for rapid and round-the-clock photocatalytic degradation of organic pollutants - Mingtong Li; Jianhua Zhou; Rui Di; Zhixiang Zhang; Xiaojiang Mu; Xiaoyang Wang; Yufei Gu; Lifen Su; Jing Liu; Chengyan Liu; Changlai Yuan; Lei Miao (Journal of Advanced Ceramics)
The highly efficient degradation and purification of organic pollutants in wastewater by photocatalysis is still challenging. In this study, a piezoelectric potential-activated interfacial electric field (IEF) was constructed to endow BiFeO3@BaTiO3 (BFO@BTO) heterojunction with the ability to serve as a round-the-clock photocatalyst for polluted water remediation. BFO@BTO heterojunction is composed of BiFeO3 nanoparticles decorated on the surface of BaTiO3 nanorods, which shortens the carrier migration path. More importantly, the IEF can be activated and reconstructed under ultrasonic wave irradiation, leading to a lower potential barrier and enhanced separation efficiency for photogenerated carriers. The degradation rate constant k value of BFO@BTO heterojunction reached 0.038 min−1, which was 1.9 and 7.0 times greater than that of piezocatalysis and photocatalysis alone, respectively. It also exhibited excellent stability in three light‒dark cycles for high concentrations (25 mg·L−1) of rhodamine B (RhB) and tetracycline hydrochloride (TC). This study provides a promising strategy for designing highly active photoassisted piezocatalysts for environmental energy utilization and round-the-clock catalysis.